2019
DOI: 10.3389/fnsys.2019.00040
|View full text |Cite
|
Sign up to set email alerts
|

Whisker-Mediated Touch System in Rodents: From Neuron to Behavior

Abstract: A key question in systems neuroscience is to identify how sensory stimuli are represented in neuronal activity, and how the activity of sensory neurons in turn is “read out” by downstream neurons and give rise to behavior. The choice of a proper model system to address these questions, is therefore a crucial step. Over the past decade, the increasingly powerful array of experimental approaches that has become available in non-primate models (e.g., optogenetics and two-photon imaging) has spurred a renewed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 376 publications
(617 reference statements)
1
56
0
Order By: Relevance
“…The significant effects on cerebrovascular function were mainly manifested as an increased response at a specific stimulation frequency (5Hz), although similar trends were indicated at other frequencies. Stimulation frequency dependent effects have been previously reported in the literature ( Spain et al., 2015 ; Martin et al., 2006 ) and for the whisker system, stimulation frequencies at around 5Hz are regarded as most effective and of functional relevance in driving somatosensory neurovascular responses in anaesthetised animals ( Martin et al., 2006 ; Adibi, 2019 ) and may therefore represent the point of maximal sensitivity to treatment effects in this study. These results underline the complexity of the neurovascular coupling relationships, and the importance of including a dynamic range of sensory stimulation in neurovascular research to better assess how the neurovascular system responds to different levels of input in health and under disease-related manipulations.…”
Section: Discussionmentioning
confidence: 53%
“…The significant effects on cerebrovascular function were mainly manifested as an increased response at a specific stimulation frequency (5Hz), although similar trends were indicated at other frequencies. Stimulation frequency dependent effects have been previously reported in the literature ( Spain et al., 2015 ; Martin et al., 2006 ) and for the whisker system, stimulation frequencies at around 5Hz are regarded as most effective and of functional relevance in driving somatosensory neurovascular responses in anaesthetised animals ( Martin et al., 2006 ; Adibi, 2019 ) and may therefore represent the point of maximal sensitivity to treatment effects in this study. These results underline the complexity of the neurovascular coupling relationships, and the importance of including a dynamic range of sensory stimulation in neurovascular research to better assess how the neurovascular system responds to different levels of input in health and under disease-related manipulations.…”
Section: Discussionmentioning
confidence: 53%
“…In agreement with previous findings ( 34 , 40 ), we found that TBI induced sensory hypersensitivity to whisker stimulation in both sexes, however, females displayed an overall lower magnitude of sensory hypersensitivity than males. The whisker barrel circuit is structurally well-organized with somatotopic arrangement that, while being a simple circuit, mediates complex behaviors ( 61 ). Our research and others demonstrate that late-onset sensory hypersensitivity after FPI parallels neuropathology, neuroinflammation, gliosis, circuit reorganization, changes in electrophysiological activity, and neurotransmission indicating a number of ongoing sequelae of events in the relays of the whisker barrel circuit leading up to the development of this aberrant behavioral phenotype ( 36 , 38 , 62 65 ).…”
Section: Discussionmentioning
confidence: 99%
“… 137 139 ) as well as spatial information such as localization in space (e.g. 134 , 140 ), as they sweep the environment by intrinsic muscles 132 ).…”
Section: Methodsmentioning
confidence: 99%
“…In order to explore a space, rodents have to move through it, as they mainly rely on their olfaction and whisker-mediated touch system to gather environmental information (e.g. [131][132][133][134][135][136] ), and transmit tactile information for object and texture recognition (e.g. [137][138][139] as well as spatial information such as localization in space (e.g.…”
Section: Capturementioning
confidence: 99%